European experience of colorectal endoscopic submucosal dissection: a systematic review of clinical efficacy and safety. (1st April 2019) - Thorlacius, Henrik; Rönnow, Carl-Fredrik; Toth, Ervin
Abstract: Background: Endoscopic submucosal dissection (ESD) is an advanced method allowing en bloc resection of large and complex lesions in colon and rectum. Herein, the European experience of colorectal ESD was systematically reviewed in the medical literature to determine the clinical efficacy and safety of colorectal ESD in Europe. Material and methods: A systematic search of PubMed for full-text studies including more than 20 cases of colorectal ESD emanating from European centres was performed. Data were independently extracted by two authors using predefined data fields, including efficacy and safety. Results: We included 15 studies containing a total of 1404 colorectal ESD cases (41% in the colon) performed between 2007 and 2018. Lesion size was 40 mm (range 24–59 mm) and procedure time was 102 min (range 48–176 min). En bloc resection rate was 83% (range 67–93%) and R0 resection rate was 70% (range 35–91%). Perforation rate was 7% (range 0–19%) and bleeding rate was 5% (range 0–12%). The percentage of ESD cases undergoing emergency surgery was 2% (range 0–6%). Additional elective surgery was performed in 3% of all cases due to histopathological findings showing deep submucosal invasion or more advanced cancer. The recurrence rate was 4% (range 0–12%) after a median follow-up time of 12 months (range 3–24 months). Conclusions: This review shows that ESD is effective and safe for treating large and complex colorectal lesions in Europe although there is room for improvement. Thus, it is important to develop standardized and high-quality educational programs in colorectal ESD in Europe.